Tinjauan Kritis terhadap Pelaksanaan Keputusan Walikota Padang Nomor 438 Tahun 2018 Mengenai Pengaturan Pedagang Kaki Lima - Nadia, Nasyatul; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2024)
The chaos and social conflict in Pasar Raya Padang prompted the government to issue Padang Mayor Decree No. 438/2018, which regulates the location and operational schedule for street vendors (PKL) in Pasar Raya. This research aims to evaluate the implementation and identify obstacles to implementing the decree. This research uses a qualitative method with a descriptive approach. Based on interviews conducted and data analysis using Dunn's evaluation theory, the results show that the implementation of this decree has yet to run optimally. The effectiveness indicator shows that efforts to control street vendors by related agencies are still slow, while the target group of this decree still complains about the policy. The adequacy indicator reveals a need for more personnel supervising the market. In contrast, the equity indicator shows that although distribution is even, there is still injustice due to ineffective communication between street vendors and officials. The responsiveness indicator also shows unsatisfactory results, and the appropriateness indicator reveals that the goal of creating urban beauty and justice for shopkeepers has yet to be achieved. The main obstacles in the implementation of this decree include: There is a need for more personnel in the field, Different patterns of enforcement due to changes in the leadership of the office, Street vendors need a better understanding of the contents of the decree, and Misuse of business premises by street vendors.